Main differences between the first and second waves of COVID-19 in Madrid, Spain - Soriano, Vicente; Ganado-Pinilla, Pilar; Sánchez-Santos, Miguel; Gómez-Gallego, Felix; Barreiro, Pablo; de Mendoza, Carmen; Corral, Octavio Jorge (International journal of infectious diseases, 2021)
Background: The emergence and rapid global spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) represents a major challenge to health services, and has disrupted social and economic activities worldwide. In Spain, the first pandemic wave started in mid-March 2020 and lasted for 3 months, requiring home confinement and strict lockdown. Following relaxation of the measures during the summer, a second wave commenced in mid-September 2020 and extended until Christmas 2020. Methods: The two pandemic waves were compared using information collected from rapid diagnostic tests and polymerase chain reaction assays at one university clinic in Madrid, the epicentre of the pandemic in Spain. Results: In total, 1569 individuals (968 during the first wave and 601 during the second wave) were tested for SARS-CoV-2-specific antibodies using fingerprick capillary blood. In addition, during the second wave, 346 individuals were tested for SARS-CoV-2-specific antigen using either oral swabs or saliva. The overall seroprevalence of first-time-tested individuals was 12.6% during the first wave and 7.7% during the second wave (P < 0.01). Seroconversions and seroreversions within 6 months occurred at low rates, both below 5%. During the second wave, 3.5% of tested individuals were SARS-CoV-2 antigen positive, with two cases considered as re-infections. Severe clinical symptoms occurred in a greater proportion of cases during the first wave compared with the second wave (27.8% vs 10.6%, respectively; P = 0.03). Conclusion: The cumulative seroprevalence of SARS-CoV-2 antibodies in Madrid at the end of 2020 was approximately 20%. Seroreversions within 6 months occurred in 4% of cases. Seroconversions and re-infections were clinically less severe during the second wave than during the first wave. Hypothetically, a lower viral inoculum as a result of social distancing, increased use of face masks, promotion of outdoor activities and restrictions on gatherings may have contributed to this lower pathogenicity.
Keywords: antibodies; coronavirus; prevalence; re-infections; SARS-CoV-2; Scopus; WOS(2)